2004
DOI: 10.1158/1078-0432.ccr-04-1261
|View full text |Cite
|
Sign up to set email alerts
|

Gain of OGP, an Estrogen-Regulated Oviduct-Specific Glycoprotein, Is Associated with the Development of Endometrial Hyperplasia and Endometrial Cancer

Abstract: Purpose: Lesions in the endometrium are difficult to differentially diagnose. The present study examined whether oviduct-specific glycoprotein is differentially expressed in normal, hyperplastic, and malignant endometrium.Experimental Design: The expression of oviduct-specific glycoprotein was characterized by immunohistochemical methods with whole sections of endometrium from 90 women. An endometrial cancer tissue microarray with 200 cases of endometrial cancer was also assessed for oviductspecific glycoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…22 We reported previously that in tumor tissue microarrays, rare endometrial carcinomas were positive for OVGP1. 19,20 These observations agree with the results of the present study. Interestingly, in an analysis of gene expression in early-stage ovarian cancer, mucinous and clear cells histotypes could be distinguished from the others regardless of tumor grade.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…22 We reported previously that in tumor tissue microarrays, rare endometrial carcinomas were positive for OVGP1. 19,20 These observations agree with the results of the present study. Interestingly, in an analysis of gene expression in early-stage ovarian cancer, mucinous and clear cells histotypes could be distinguished from the others regardless of tumor grade.…”
Section: Discussionsupporting
confidence: 93%
“…As detection antibody, we used a highly specific polyclonal rabbit antiYhuman OVGP1 antibody. 13,19,20 Construction of Double-Determinant (Sandwich) Enzyme-Linked Immunosorbent Assay…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…NAC1 may play an important role in estrogen-induced cell growth in normal cyclic endometrium. It may be less important in endometrial cancers that have lost estrogen signaling and are stimulated by other oncogenic pathways (28,32,33). While many endometrial cancers lose NAC1 expression, some high grade tumors continue to produce it.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, like tubulin up-regulation at ciliogenesis (Shea and Walsh 1987), OGP is coordinately regulated by genes involved in differentiation and/or proliferation suppression (Bauersachs et al 2004). Further, it is expressed ex situ in the endometrium (Punyadeera et al 2005;Talbi et al 2006), wherein the loss is correlated with neoplastic progression involving de-differentiation and proliferation (Woo et al 2004). Additionally, in vitro studies have revealed a close link between OGP mRNA levels and the maintenance of polarity and differentiation (Reischl et al 1999).…”
Section: Introductionmentioning
confidence: 99%